Dampak Inflasi, Suku Bunga, dan Nilai Tukar Terhadap Harga Saham - Nurhasanah, Andi; Kahfi, Zul (CV. Ulil Albab Corp, 2025)
This study aims to examine the effects of inflation, interest rates, and exchange rates on stock prices in metal and mineral mining companies listed on the Indonesia Stock Exchange (IDX). The data for this research was obtained from the financial reports of metal and mineral mining companies listed on the IDX. The study uses secondary data collected through observations made at the Capital Market Information Center (PIPM). The data analysis method used is multiple linear regression analysis. The results indicate that, partially, the variables inflation, interest rates, and exchange rates have a negative and significant effect on stock prices.